2022
DOI: 10.1096/fj.202200460r
|View full text |Cite
|
Sign up to set email alerts
|

Short duration treadmill exercise improves physical function and skeletal muscle mitochondria protein expression after recovery from FOLFOX chemotherapy in male mice

Abstract: FOLFOX (5‐FU, leucovorin, oxaliplatin) is a chemotherapy treatment for colorectal cancer which induces toxic side effects involving fatigue, weakness, and skeletal muscle dysfunction. There is a limited understanding of the recovery from these toxicities after treatment cessation. Exercise training can improve chemotherapy‐related toxicities. However, how exercise accelerates recovery and the dose required for these benefits are not well examined. The purpose of this study was to examine the effect of exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Animal models with tumor and anticancer therapy recapitulate the clinical scenario; however, most studies concerned cancer treatment in otherwise healthy animals. Last, cancer therapies are often used clinically in multidrug regimens and to date only Halle et al [45] attempted to use a regimen (FOLFOX) in an experimental system. Thus, no comment can be made regarding the possible interaction when multiple agents are used together.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models with tumor and anticancer therapy recapitulate the clinical scenario; however, most studies concerned cancer treatment in otherwise healthy animals. Last, cancer therapies are often used clinically in multidrug regimens and to date only Halle et al [45] attempted to use a regimen (FOLFOX) in an experimental system. Thus, no comment can be made regarding the possible interaction when multiple agents are used together.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 99%
“…However, few studies of treatment or prevention of systemic cancer therapy-induced myopathy are available and for now most evidence is from animal models. Therapeutics with evidence for efficacy include eicosapentaenoic acid [42], 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) [48], a soy-derived isoflavone (daidzein) [37], exercise [45], a proteasome inhibitor (bortezomib) [41], and Chinese herbal medicine formula Yifei sanjie [46]. As all these results have been obtained in single studies and the animal models in which they were conducted are of unknown translational relevance, further investigation is needed.…”
Section: Therapeutic Strategies To Mitigate Systemic Cancer Therapy-i...mentioning
confidence: 99%
“…The most clinically relevant outcome would be the recurrence of overt disease (22). Exercising animals after chemotherapy treatment has been shown to be feasible, however, these studies have typically focused on chemotherapy toxicities and, therefore, used non-tumor-bearing animals (27).…”
Section: Scenario #3: Previously Treated Micrometastasesmentioning
confidence: 99%
“…, leucovorin, oxaliplatin) chemotherapy is a regimen used to treat colorectal cancer that can cause long-lasting metabolic dysfunction, skeletal muscle mitochondria damage, fatigue and weakness in clinical and preclinical models (Denlinger and Barsevick, 2009;Barreto et al, 2016;Chung et al, 2020;Halle et al, 2023). We previously demonstrated that shortduration treadmill exercise performed regularly over two-weeks improves fatigue resistance in mice after the cessation of FOLFOX chemotherapy (Halle et al, 2022). However, it is unclear if prior treatment with FOLFOX alters the fasting regulation of circulating metabolic regulators and skeletal muscle myokine/exerkine-related exercise adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…Early adaptations to repeated exercise sessions were investigated in healthy mice using treadmill exercise performed for either 10 min/d (short) or 55 min/d (long) durations, 6 days a week for 14 total sessions. A subset of mice performed treadmill exercise after completing 4 cycles of FOLFOX chemotherapy, which has previously been shown to induce deficits in physical function and systemic metabolism (Halle et al, 2022;Halle et al, 2023). Mice were sacrificed 48-72 h after the last treadmill session to limit the acute effects of the last exercise bout.…”
Section: Introductionmentioning
confidence: 99%